2021
DOI: 10.3389/fevo.2021.584872
|View full text |Cite
|
Sign up to set email alerts
|

Living at the Edge: Increasing Stress for Plants 2–13 Years After the Retreat of a Tropical Glacier

Abstract: Rapid warming is a major threat for the alpine biodiversity but, at the same time, accelerated glacial retreat constitutes an opportunity for taxa and communities to escape range contraction or extinction. We explored the first steps of plant primary succession after accelerated glacial retreat under the assumption that the first few years are critical for the success of plant establishment. To this end, we examined plant succession along a very short post-glacial chronosequence in the tropical Andes of Ecuado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 65 publications
5
24
0
Order By: Relevance
“…On the Antisana volcano, about 63 km southeast of our study site, Moret et Time is an essential variable in warming experiments. OTCs accelerate the rate to visualize change compared to prolonged comparative studies (Porro et al, 2019;Steinbauer et al, 2020;Anthelme et al, 2021), and our study found significant changes after 7 years of sampling. However, studies in non-tropical ecosystems found differences in a much shorter timeframe; for example, studies in tundra found changes in plant communities after two growing seasons (Walker et al, 2006).…”
Section: Relationship Between Biomass Biodiversity and Growth Formssupporting
confidence: 42%
“…On the Antisana volcano, about 63 km southeast of our study site, Moret et Time is an essential variable in warming experiments. OTCs accelerate the rate to visualize change compared to prolonged comparative studies (Porro et al, 2019;Steinbauer et al, 2020;Anthelme et al, 2021), and our study found significant changes after 7 years of sampling. However, studies in non-tropical ecosystems found differences in a much shorter timeframe; for example, studies in tundra found changes in plant communities after two growing seasons (Walker et al, 2006).…”
Section: Relationship Between Biomass Biodiversity and Growth Formssupporting
confidence: 42%
“…The rapid shrinkage of tropical glaciers induces an accelerated reduction of glacial influence in adjacent ecosystems, and may have considerable consequences on biodiversity. The decrease in meltwater supply reduces aquatic habitat availability for aquatic species (Milner et al 2017), and increases the risk of desiccation for terrestrial habitats (Breen and Levesque 2006, Anthelme et al 2021). Indeed, as precipitation gradient along elevations is often inverted in the tropics (Leuschner 2000, Anthelme and Dangles 2012), tropical alpine plants rely significantly on ground surface water sourcing from glacier melting.…”
Section: Discussionmentioning
confidence: 99%
“…Glacier retreat rates have accelerated in the last five decades (Zemp et al, 2019), while there is increasing evidence that alpine species distributions are shifting upward (Lenoir and Svenning, 2015). This offers a unique opportunity to study climate change impacts in high mountain environments and opens up important questions regarding the development of novel ecosystems and the ability of high elevation specialists to become established and to maintain viable populations in newly exposed areas (Cannone et al, 2008;Zimmer et al, 2018;Cuesta et al, 2019;Anthelme et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In tropical alpine regions additional limiting factors include reduced plant protection from seasonal snow and particularly fast rates of highelevation warming and glacier retreat (Rabatel et al, 2013;Wang et al, 2016;Vuille et al, 2018). However, studies of the patterns and mechanisms of primary succession in glacier forefields are scarce in the alpine tropics (see Spence, 1989;Mizuno, 2005;Mizuno and Fujita, 2014;Suárez et al, 2015;Zimmer et al, 2018;Anthelme et al, 2021;Rosero et al, 2021), especially under the harsh conditions that occur in mountains where they are about to become extinct.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation